ANALISIS PROFITABILITAS USAHA SAMBAL IKAN ROA PADA INDUSTRI SOFIE LOCALFOOD DI KOTA PALU - Farida Farida; Hardiyanti Sultan (Fakultas Pertanian, Universitas Tadulako, 2022)
The purpose of the study was to assess the income and profitability of the roa fish sauce business in the Local Food Sofie Industry in Palu city. The study was conducted from July to December 2020 and involved four workers as respondents, who were purposively selected. The research was analyzed quantitatively, including Return on Investment (ROI) and Return on Equity Analysis. The findings showed that the total production costs incurred over the six months from July to December were IDR 62,023,789. The sales generated revenue for the same period were IDR 99.810.000, resulting in an income of IDR 37,787,211 for the six-month period. The profitability analysis revealed that the return on investment achieved during the July to December period was 60.15%. This indicates that for every IDR 100,000 invested in the roa fish sauce business, a profit of IDR 60.150 was generated. The return on equity achieved by the business over the last six months was 67.60%. This implies that for every IDR 100,000 of sales, a profit of IDR 67,600 was obtained. Overall, the study shows that the roa fish sauce business in the Local Food Sofie Industry is profitable and generates a reasonable return on investment and equity.